2018
DOI: 10.1002/slct.201802242
|View full text |Cite
|
Sign up to set email alerts
|

Radiolytic Synthesis of Cyanogen Chloride, Cyanamide and Simple Sugar Precursors

Abstract: Chemical evolution, from simple molecules to complex systems, is fundamental to modern origins of life research, and complex reaction networks are often supposed to have operated on the early Earth. Herein, a variety of compounds useful particularly for RNA synthesis − namely, cyanogen chloride, cyanamide, and nitrile precursors to simple sugars − are produced in short order by a chemical reaction network starting from hydrogen cyanide and driven by gamma radiolysis. The radiolytic yield of cyanamide was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 70 publications
1
18
0
2
Order By: Relevance
“…Methanimine, formaldehyde, acetaldehyde, and 2-iminoethanol are inferred by the observation of aminoacetonitrile, glycolonitrile, lactonitrile, and serinenitrile, respectively, while glycolaldehyde is inferred from the direct NMR detection of its gem-diol form. Cyanogen chloride was observed in previously reported(35) radiolysis experiments under similar high NaCl concentrations. For further details of the proposed mechanisms, see SI Appendix, Schemes.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Methanimine, formaldehyde, acetaldehyde, and 2-iminoethanol are inferred by the observation of aminoacetonitrile, glycolonitrile, lactonitrile, and serinenitrile, respectively, while glycolaldehyde is inferred from the direct NMR detection of its gem-diol form. Cyanogen chloride was observed in previously reported(35) radiolysis experiments under similar high NaCl concentrations. For further details of the proposed mechanisms, see SI Appendix, Schemes.…”
supporting
confidence: 56%
“…Both sources of energy have been shown capable of generating solvated electrons (eaq ) in aqueous environments, and in the case of γ rays, ionization of water is what leads to eaq in addition to hydroxyl radical (•OH) and hydrogen atom (•H) production. The generation of eaq in the presence of excess HCN has been shown to lead to simple sugars (35)(36)(37). This reaction works by a Kiliani-Fischer homologation mechanism, whereby eaq effectively serves as the reducing agent.…”
Section: Radiolysis As a Driving Forcementioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that radiolysis, by means of a continuous reaction network, generates a complex mixture of products that includes precursors for nucleotide synthesis 48 . These findings add to a growing body of evidence that radicals provide particularly efficient means of connecting geochemical substrates to macromolecular precursors with minimal experimental intervention 2 , 12 , 49 54 . Here we analyse the structure of a reaction network compiled from hundreds of experiments conducted over 60 years of research that links common geochemical substrates (CO 2 , H 2 O, N 2 , NaCl, chlorapatite and pyrite) to radiolytically-produced prebiotic precursors, and compare this network to life and its ecologies 55 57 .…”
Section: Introductionmentioning
confidence: 53%
“…Amino acids are produced through a combination of radiolysis and acid-hydrolysis of uncharacterised polymers 2 , 61 . Nucleotide precursors that lead to cytidine and uridine cyclic phosphates are all present within the network 48 , 49 , 62 .
Figure 1 Visualisation and statistical analysis of radiolysis network.
…”
Section: Resultsmentioning
confidence: 99%